Post activation potentiation - Changes in power development in upper body pulling, following maximal force exercise - Olsen, R.; Soerensen, H. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The contractile response in skeletal muscle depends partly on the contractile history, which can have both a fatiguing and a potentiating effect. The balance between these decides whether the muscle`s contractile response in the post phase is increased (post activation potentiation, PAP), decreased, or unchanged (Rassier & MacIntosh, 2000). Young et al (1998) and Gilbert & Lees (2005) have shown that PAP can comprise increase in rate of force development (RFD) and maximal power (Pmax). Various intervention protocols have been used to examine PAP in the lower body and in the upper body pushing muscles, i.e. shoulder flexors and elbow ectensors, with varying results. However, no one has so far investigated PAP in the upper body pulling muscles, i.e. shoulder extensors and elbow flexors.Thus, the purpose of this study was to examine RFD and Pmax in the upper body pulling muscles following a bench-pull intervention. Methods: 8 elite (national medal takers) male sprint canoeing and sprint swimming athletes, whit 3-14 years of continued strength training experience, where chosen, all had employed the exercise used in the study as a main exercise in their strength training for at least 6 month prior to the study. The participants visited the lab on two occasions separated by 1-4 days. On the first occasion the subjects´ 1RM bench-pull was determined. On the following test occasion, an intervention of 5x1RM was performed whit 5min rest in between. Pre and at 1,7,13, and 19min post the intervention, the subjects performed 3 explosive bench-pulls with 1min rest in between with 40% 1RM. The Pre and post tests were high speed filmed and subsequently Pmax from each pull was calculated. The mean value from each set of 3 pulls were used for further analysis. A one way ANOVA with repeated measures was used to test for significant differences among pre and post intervention Pmax. Results: None of the participants could complete all the lift successfully during the intervention protocol, only 2 of the participants could complete more than 1 lifts successfully. Results showed no significant difference in Pmax from pre to any of the post measurements. Discussion: The results in this study conflict with the earlier results found in the lower body by Gilbert & Lees, but is similar to result found by (Farup & Sørensen,2008) in upper body, both using the exact same intervention. It could be speculated if it for elite athletes is possible to reproduce a true 1RM 5 times whit only 5min break in between. Or if different tolerance for maximum intensity levels in the upper body vs. the lower body could explain the conflicting results. In conclusion, the results shows that an intervention of 1RM is not applicable, to elicit post activation potentiation